New Optimization Strategies on Radiation Protection in Fluoroscopy-Guided Interventional Procedures in Pediatrics - Carlos Ubeda (MDPI AG, 2023)
The term fluoroscopically guided interventional procedure describes a clinical practice in medicine, where fluoroscopic systems are used to conduct diagnostic procedures or provide image guidance for therapeutic interventional procedures performed via percutaneous or other access routes [...]